(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The efficiency of corona discharge (CD) for detoxification of aflatoxin B1 (AB1), ochratoxin A (OA), and fumonisin B1 (FMB1) from poultry feeds with its influences on feed components was investigated. Materials and Methods: Feed samples were exposed to CD for six durations (10, 20, 30, 40, 50, and 60 min) at three distances (1.5, 2.5, and 3.5 cm). Mycotoxin levels were estimated by competitive enzyme-linked immunosorbent assay, and findings were substantiated by high-performance liquid chromatography. Results: AB1, OA, and FMB1 degradation percentages increased significantly (p < 0.05) with processing times increment and distances reduction to reach values of 83.22%, 84.21%, and 84.76% at the first distance; 80.28%, 84.00%, and 84.12% at the second distance; and 68.30%, 71.74%, and 76.18% at the third distance, respectively, after 60 min of treatment. FMB1 reported the highest degradation level. Concerning CD impacts on feed composition, protein, fat, and moisture contents decreased significantly (p < 0.05). Carbohydrates and ash were not affected adversely. Depending on peroxide values estimation, fats were of good quality. Conclusion: The CD effectiveness for AB1, OA, and FMB1 detox from poultry feeds with moderate impact on the quality of feed. J. Adv. Vet. Anim. Res., 11(4): 819–834, December 2024 http://doi.org/10.5455/javar.2024.k834